IL‐13‐producing BLT1‐positive CD8 cells are increased in asthma and are associated with airway obstruction. Issue 5 (10th April 2013) - Dakhama, A.; Collins, M. L.; Ohnishi, H.; Goleva, E.; Leung, D. Y. M.; Alam, R.; Sutherland, E. R.; Martin, R. J.; Gelfand, E. W.
Abstract Background The role of CD8 T lymphocytes in the pathogenesis of asthma is not well understood. We investigated whether a subset of IL‐13‐producing BLT1‐positive CD8 T lymphocytes are present in asthmatic airways and are associated with impaired lung function. Methods Bronchoalveolar lavage (BAL) cells were obtained from asthmatic (n = 39) and healthy control (n = 28) subjects. Cells were stimulated with phorbol ester and ionomycin in the presence of brefeldin A and stained for CD8, BLT1, and intracellular IL‐13. The frequency of IL‐13‐producing BLT1‐positive CD8 T lymphocytes was compared between the two groups and related to lung function, serum IgE levels, and reticular basement membrane (RBM) thickness. Results A subset of CD8 T lymphocytes expressing BLT1 and producing IL‐13 were detected in the airways of all asthmatic subjects. The frequency of this subset among recovered lymphocytes was significantly higher in the airways of asthmatic subjects compared with controls (mean ± SEM: 16.2 ± 1.4 vs 5.3 ± 0.5, respectively, P < 0.001) and correlated positively with serum IgE levels and RBM thickness. More importantly, the frequency of CD8 T lymphocytes co‐expressing BLT1 and IL‐13 was inversely related to FEV1 and FEF[25–75] percent predicted values (P < 0.001). Conclusions A subset of CD8 T lymphocytes expressing BLT1 and producing IL‐13 is present in the airways of asthmatics. The accumulation of these cells is associated with airway obstruction, suggesting that they may play a significant pathogenic role in bronchial asthma.